IKLIM KOMUNIKASI ORGANISASI DAN MOTIVASI KERJA PIMPINAN DALAM MEWUJUDKAN MISI PERUSAHAAN - Satria Kusuma (Universitas Muhammadiyah Jakarta, 2018)
The objectives of this research are to observe and analyze climate organizational communication and leadership motivation performance in achieving corporate mission of PLN Inc. Surakarta. The method used for this research is descriptive qualitative. The analysis proves that the communication climate in PLN Inc is supporting the leadership motivation performance. Several supporting factors of the finding are trust, support, honesty, and transparency among the leaders of the top, middle and lower level. Humans are motivated by communication climate and creative and participative working system, when someone has sense of belonging, automatically, they will support the process of achieving the corporate mission. A satisfying communication climate can be achieved through creating a shared vision to assure the free flow of information and allow subordinates to participate in decision making processes. Meanwhile, the existing organizational climate is formed through several factors; responsibility, organizational or management structure which is tailored based on the needs of companies, and working motivation from the leaders so that every problem can be solved through solid teamwork to achieve the corporate mission. Keywords: organizational communication, communication climate, working motivation